Analysis of Factors Affecting Inflation in Indonesia: an Islamic Perspective - Elis Ratna Wulan; Sofia Nurfaiza (UIN Sunan Gunung Djati Bandung, 2014)
This study aims to determine the factors affecting inflation. The research is descriptive quantitative in nature. The data used are reported exchange rates, interest rates, money supply and inflation during 2008-2012. The research data was analyzed using multiple linear regression analysis. The results showed in the year 2008-2012 the condition of each variable are (1) the rate of inflation has a negative trend, (2) the interest rate has a negative trend, (3) the money supply has a positive trend, (4) the value of exchange rate has a positive trend. The test results by using multiple linear regression analysis result that variable interest rates, the money supply and the exchange rate of the rupiah significant effect on the rate of inflation.